Tetrandrine Suppresses Transient Receptor Potential Cation Channel Protein 6 Overexpression- Induced Podocyte Damage via Blockage of RhoA/ROCK1 Signaling [Corrigendum] - Yu J; Zhu C; Yin J; Yu D; Wan F; Tang X; Jiang X (Dove Medical Press, 2020)
Yu J, Zhu C, Yin J, et al. Drug Des Dev Ther. 2020;14:361–370.The authors have advised that in Figure 3 on page 365, the image of the Blank group was mistakenly duplicated from the NC group.Read the original article